State Recognition and the Dangers of Race Shifting - Leroux, Darryl (American Indian Culture and Research Journal, 2023)
This article examines the claims to an Indigenous identity made by the four state-recognized Abenaki tribes in Vermont through an analysis of their petition for federal acknowledgement (1982–2005) and applications for state recognition (2010–2012). A detailed analysis of their claims demonstrates that the tribes are not Abenaki, but instead, represent the descendants of French Canadians who immigrated to the Champlain Valley of northwestern Vermont in the mid-nineteenth century. In this case study of what the anthropologist Circe Sturm has called “race shifting,” I demonstrate how the politics of recognition, which do not include the kin-making and relations of Indigenous nations, serve the interests of settler colonialism under the guise of decolonization. I attribute the emergence of race shifting along three vectors: the move away from white identity post-Civil Rights era; the lack of a tribal presence in Vermont; and the flaws in the state recognition process.